SPECTROPHOTOMETRIC DETERMINATION OF POLYPHENOLIC AND PROTEIN CONTENT OF YOUNG WHITE WINES IN THE MOLDOVA AREA - ANDREEA HORTOLOMEU; IURIE SCUTARU; ALEXANDRA ARSENI; RODICA STURZA; ILEANA DENISA NISTOR (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In this paper, the processes of protein stability were treated in order to identify the level of protein substances as well as the polyphenolic compounds in white wines. For an optimal determination of the oxidation degree, respectively of the protein stability, a sample of 6 types of white wine from different grape varieties was chosen for analysis. For the heat treatment of protein stability has not yet materialized and published a working protocol in the literature, because many researchers in the field of vinification use different time intervals and temperature. In this paper, the method of thermal stability of proteins was used in two different working environments, respecting the same temperature and time: in the water bath and thermostat. By this method can be deduced the optimal amount of stabilizing agent for the removal of unstable proteins at high temperatures, being less affected by the presence of other polyphenolic compounds, metal cations and the pH of wine. The polyphenolic oxidation method was used to determine the degree of oxidability of the wines.